Problems of legal regulation of cross-border insolvency - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article deals with modern legal problems of cross-border insolvency (bankruptcy), the institute of recognition of foreign bankruptcies, analyzed the characteristics and some features of its decision in the national jurisdiction